Multi-Scale Group Transformer for Long Sequence Modeling in Speech Separation - Zhao, Yucheng; Luo, Chong; Zha, Zheng-Jun; Zeng, Wenjun (International Joint Conference on Artificial Intelligence, 2020)
.